2006
DOI: 10.1128/mcb.26.2.605-616.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Lrp1 Knock-In Mice Generated by Recombinase-Mediated Cassette Exchange Reveal Differential Importance of the NPXY Motifs in the Intracellular Domain of LRP1 for Normal Fetal Development

Abstract: Lrp1 knock-in mice carrying either a wild-type allele or three different mutated alleles encoding the multifunctional endocytic receptor LRP1 were generated by recombinase-mediated cassette exchange (RMCE). Reinsertion by RMCE of a wild-type allele led to a normal pattern and level of gene expression and a completely normal phenotype, indicating that the RMCE procedure itself is neutral with respect to the function of the gene locus. In contrast, reinsertion of mutated LRP1 alleles carrying either inactivating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…We could anticipate, in accordance with recent data (Roebroek et al, 2006), that natural mutants affecting those critical sorting motifs that we have defined, especially the proximal NPxY, would be relatively unviable.…”
Section: Discussionsupporting
confidence: 64%
“…We could anticipate, in accordance with recent data (Roebroek et al, 2006), that natural mutants affecting those critical sorting motifs that we have defined, especially the proximal NPxY, would be relatively unviable.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the efficiency of RMCE-mediated knock-in recombination was very high in our screening (44 to 87%), compared with conventional homologous recombination. This is similar to or higher than the efficiencies previously reported for RMCE using the Cre-lox system (Araki et al, 2006;Liu et al, 2006;Toledo et al, 2006) or the Flp-FRT system (Cesari et al, 2004;Roebroek et al, 2006). In our RMCE procedure, we replaced a 1.0 kb genomic sequence with knock-in sequences containing mutant lox sites and an FRT-flanked Puro.…”
Section: Discussionmentioning
confidence: 84%
“…The distal NPXY 4507 motif has been shown to bind signaling proteins (10,16,25), and the proximal NPXY 4473 motif has been shown to be involved in receptor recycling and demonstrated a strong phenotype in knock-in mice (7,8). Binding of Shc and Dab1 has been localized to the NPXY 4507 motif and a few surrounding residues using peptides as the pull-down bait (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational studies identified the YXXL motif (which overlaps with Tyr 4507 ) as critical for LRP1 receptor endocytosis (6). Recently, the membrane proximal NPXY motif has been identified as the binding site for Snx17 (sorting nexin 17), and knock-in experiments in mice showed a strong phenotype upon mutation of this site (7,8). Mutation of Tyr 4473 to alanine, which abolishes Snx17 binding, resulted in impaired receptor recycling and reduced amounts of the mature form of LRP1 on the cell surface (7).…”
mentioning
confidence: 99%